2020
DOI: 10.3389/fcell.2020.582370
|View full text |Cite
|
Sign up to set email alerts
|

Histone Deacetylase Inhibition in Non-small Cell Lung Cancer: Hype or Hope?

Abstract: Epigenetic modulation, including acetylation, methylation, phosphorylation, and ubiquitination, plays a pivotal role in regulation of gene expression. Histone acetylation—a balance between the activities of histone acetyltransferases (HATs) and histone deacetylases (HDACs)—is one of the key epigenetic events. Our understanding of the role of HDACs in cancer is evolving. A number of HDAC isoenzymes are overexpressed in a variety of malignancies. Aberrant histone acetylation is associated with dysregulation of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
42
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(43 citation statements)
references
References 92 publications
1
42
0
Order By: Relevance
“…Numerous studies indicated that IFIT2, a tumor suppressor gene, inhibited tumor growth, metastasis and induced cell apoptosis in many cancers like oral squamous carcinoma, colorectal cancer, leukemia, osteosarcoma and hepatocellular carcinoma [24]. In present study, we found that high expression of HDAC5, as well as low expression of P300 in glioma cells, decreased acetylation of IFIT2, then upregulated its ubiquitination and degradation, consequently promoting growth, metastasis and stemness of glioma.…”
Section: Discussionsupporting
confidence: 56%
“…Numerous studies indicated that IFIT2, a tumor suppressor gene, inhibited tumor growth, metastasis and induced cell apoptosis in many cancers like oral squamous carcinoma, colorectal cancer, leukemia, osteosarcoma and hepatocellular carcinoma [24]. In present study, we found that high expression of HDAC5, as well as low expression of P300 in glioma cells, decreased acetylation of IFIT2, then upregulated its ubiquitination and degradation, consequently promoting growth, metastasis and stemness of glioma.…”
Section: Discussionsupporting
confidence: 56%
“…The authors proposed that cytoplasm-localized SIRT1 downregulation may represent a novel therapeutic target to inhibit cisplatin resistance in cisplatin-resistant NSCLC cells ( 108 ). A review of the topic of histone deacetylase inhibition in NSCLC indicated that a SIRT1-mediated survival advantage may represent another mechanism through which NSCLC cells develop resistance to EGFR-TKIs ( 109 ), possibly through mediated by regulating the oxidative phosphorylation of mitochondria in lung adenocarcinoma cells, and then selectively eliminating TKI-resistant cancer stem cells.…”
Section: The Association Of Sirt1 With Hypoxia-induced Chemoresistance In Nsclcmentioning
confidence: 99%
“…Combining coexpression analysis and the CMap database, we identified four small-molecule drugs which might facilitate the treatment of LUAD, including quinostatin, MS-275, daunorubicin, and menadione. Clinical trials have explored the use of MS-275, a histone deacetylase inhibitor (HDACi), to reverse drug resistance and enhance clinical efficacy (43), while menadione (vitamin k3) is widely used in the treatment of coagulation disorders. Recent studies have reported that menadione reduced the risk of cancer through antiproliferative, autophagic, and proapoptotic effects (44,45).…”
Section: Discussionmentioning
confidence: 99%